Skull‐base surgery during the COVID‐19 pandemic: the Italian Skull Base Society recommendations. Issue 8 (15th June 2020) - Castelnuovo, Paolo; Turri‐Zanoni, Mario; Karligkiotis, Apostolos; Battaglia, Paolo; Pozzi, Fabio; Locatelli, Davide; ,; Bernucci, Claudio; Iacoangeli, Maurizio; Krengli, Marco; Marchetti, Marcello; Pareschi, Roberto; et al.
Abstract: Severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2), which causes coronavirus disease 2019 (COVID‐19), is highly contagious with devastating impacts for healthcare systems worldwide. Medical staff are at high risk of viral contamination and it is imperative to know what personal protective equipment (PPE) is appropriate for each situation. Furthermore, elective clinics and operations have been reduced in order to mobilize manpower to the acute specialties combating the outbreak; appropriate differentiation between patients who require immediate care and those who can receive telephone consultation or whose treatment might viably be postponed is therefore crucial. Italy was 1 of the earliest and hardest‐hit European countries and therefore the Italian Skull Base Society board has promulgated specific recommendations based on consensus best practices and the literature, where available. Only urgent surgical operations are recommended and all patients should be tested at least twice (on days 4 and 2 prior to surgery). For positive patients, procedures should be postponed until after swab test negativization. If the procedure is vital to the survival of the patient, filtering facepiece 3 (FFP3) and/or powered air purifying respirator (PAPR) devices, goggles, full‐face visor, double gloves, water‐resistant gowns, and protective caps are mandatory. For negative patients, use of at least an FFP2 mask is recommended. In all cases the use of drills, which promote the aerosolization of potentially infected mucous particles, should be avoided. Given the potential neurotropism of SARS‐CoV‐2, dura handling should be minimized. It is only through widely‐agreed protocols and teamwork that we will be able to deal with the evolving and complex implications of this new pandemic.